Advancing Biodiversity Monitoring by Integrating Multimodal AI Models into Camera Trap Workflow - Alencar, Luiz; Cunha, Fagner; dos Santos, Eulanda M. (Journal of the Brazilian Computer Society, 2026)
Camera trap is an important non-invasive technique for wildlife monitoring. A typical camera-trap workflow involves various relevant tasks, such as filtering empty images, classifying animal species and identifying animal behavior. In this study, we explore the application of large-scale multimodal language models (MLLMs) for processing camera trap images to perform these three tasks. We evaluate the performance of four state-of-the-art models across these tasks, precisely BLIP, CLIP, Gemini, and GPT with zero-shot and few-shot learning methodologies. Our experiments showed several interesting results. First, few-shot learning significantly enhanced model performance in filtering empty images, with BLIP achieving a much higher accuracy (91.0%) compared to only 7.61% of its zero-shot counterpart. In the task of animal species classification, Gemini showed strong baseline performance, reaching 75.89 % of accuracy with zero-shot. In terms of identifying animal behavior, two scenarios were investigated: using single image or sequences of images. The results indicate that sequence-based processing improves behavioral analysis, with BLIP attaining the highest accuracy (75.57 %) in this task. In general, our study emphasizes the limitations of the zero-shot approach in complex tasks while highlights the effective potential of few-shot and sequence-based learning to address challenging problems such as empty images, and species misclassifications. These findings demonstrate the efficacy of advanced MLLMs in automating biodiversity monitoring, offering a scalable and accurate solution for processing large-scale datasets, and advancing conservation science.